Extranodal intraosseous Rosai–Dorfman disease in the lower jaw: a case report and review of the literature - X. Yang; S. R. Gvetadze; K. D. Ilkaev; M. Lv; J. Sun; J. Li (Опухоли головы и шеи, 2018)
Rosai–Dorfman disease or sinus histiocytosis is a rare entity which may affect various lymph node groups. Extranodal form is observed in 45 % of cases, facial bone involvement is especially rare. A 62-year old male presented with complaints on dumb sensation of the chin and lower lip. After clinical assessment and surgical exploration an intraosseous extranodal Rosai–Dorfman disease was diagnosed. The patient under-went free fibula osseous graft reconstruction. After 2 years the patient is recurrent free. The purpose of this publication is to describe a rare case of lower jaw involvement in an intraosseous form with significant bone destruction. The clinical and microscopic features of the process are discussed.